2021
DOI: 10.1021/acs.jpcc.1c08962
|View full text |Cite
|
Sign up to set email alerts
|

A Near-Room-Temperature Hybrid Organic–Inorganic Lead Halide Perovskite Ferroelectric [BrCH2CH2N(CH3)3][PbBr3] and Its Flexible Composite Film

Abstract: A hybrid organic–inorganic lead halide perovskite, [BrCH2CH2N­(CH3)3]­[PbBr3] (BEPbBr), obtained by matching a quasi-spherical (2-bromoethyl) trimethylammonium cation with an infinite one-dimensional zigzag [PbBr3]− anion chain, exhibits a reversible ferroelectric phase transition at 302/286 K. Switchable dielectric and ferroelectricity were observed accompanied by the order–disorder phase transition at near-room-temperature. Further, the ferroelectric BEPbBr was dispersed into a PVDF matrix to form flexible B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The single crystal X-ray diffraction data of 1 were collected at 296 K and 410 K. At 296 K, 1 crystallizes in the monoclinic crystallographic system and is a 4 H -hexagonal perovskite structure as reported in many references. 25,26,28,29 The centrosymmetric space group of 1 is P 2 1 / c and the cell parameters of 1 is a = 10.8678(4) Å, b = 35.6850(15) Å, c = 7.7853(3) Å, Z = 8, β = 100.9530(10)° and V = 2964.3(2) Å 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The single crystal X-ray diffraction data of 1 were collected at 296 K and 410 K. At 296 K, 1 crystallizes in the monoclinic crystallographic system and is a 4 H -hexagonal perovskite structure as reported in many references. 25,26,28,29 The centrosymmetric space group of 1 is P 2 1 / c and the cell parameters of 1 is a = 10.8678(4) Å, b = 35.6850(15) Å, c = 7.7853(3) Å, Z = 8, β = 100.9530(10)° and V = 2964.3(2) Å 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The single crystal X-ray diffraction data of 1 were collected at 296 K and 410 K. At 296 K, 1 crystallizes in the monoclinic crystallographic system and is a 4Hhexagonal perovskite structure as reported in many references. 25,26,28,29 The centrosymmetric space group of 1 is P2 It can be seen from the packing view (Fig. 2), every Pb atom lies on a 2 1 -screw axis and bridges with six Br atoms, forming infinite one-dimension [PbBr 3 ] − chains along the c-axis.…”
Section: Single Crystal Structure Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic–inorganic hybrid materials (OIHMs) are a hot scientific topic due to their adjustable structure, easy synthesis, and functional features. Compared with traditional pure organic or inorganic materials, OHIMs possess more advanced properties. As one unique property of OHIMs, structural phase transition receives tremendous attention, which can introduce attractive properties, such as switchable dielectric and nonlinear optical switching. Thus, the OHIMs have great application prospects such as data communications, optoelectronic equipment, memories, actuators, sensors, and capacitors. …”
Section: Introductionmentioning
confidence: 99%
“…Recently reported organic–inorganic hybrid one-dimensional perovskite [BrCH 2 CH 2 N(CH 3 ) 3 ][PbBr 3 ] exhibits near-room-temperature ferroelectricity. 33 The structure of hybrid metal halide perovskites can be tailored by changing the organic component, central metal, and halide ion. It has been found that the replacement of halide ions in perovskites containing [(CH 3 ) 3 NCH 2 X] (X = F, Cl, Br, I) is a useful method to meet the momentum matching and tailor ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%